2007
DOI: 10.1007/s00417-007-0579-4
|View full text |Cite
|
Sign up to set email alerts
|

Morphologically functional correlations of macular pathology connected with epiretinal membrane formation in spectral optical coherence tomography (SOCT)

Abstract: SOCT pictures of eyes with ERM are diverse. Thanks to high-resolution and 3D scanning protocols, more information can be gathered. Morphological changes in the retina, such as oedema with cystic spaces, lamellar macular holes, macular pseudoholes and photoreceptor defects, were present in patients with ERM. Estimation of those changes may be an important prognostic factor in cases of epiretinal membranes.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

5
95
0
14

Year Published

2010
2010
2016
2016

Publication Types

Select...
4
4

Relationship

0
8

Authors

Journals

citations
Cited by 153 publications
(114 citation statements)
references
References 30 publications
5
95
0
14
Order By: Relevance
“…A similar association was found by Massin et al, who analyzed the postoperative visual acuity against retinal thickness changes in patients with ERM [21]. However, Michalewski observed that visual acuity in patients with ERM appears to be correlated to CRT [14].…”
Section: Discussionsupporting
confidence: 79%
See 1 more Smart Citation
“…A similar association was found by Massin et al, who analyzed the postoperative visual acuity against retinal thickness changes in patients with ERM [21]. However, Michalewski observed that visual acuity in patients with ERM appears to be correlated to CRT [14].…”
Section: Discussionsupporting
confidence: 79%
“…Prognosis for vision improvement depends on ellipsoid layer abnormalities and the external limiting membrane (ELM) disruption [11,13]. The evaluation of these zones is particularly important prior to vitrectomy, in patients with macular hole, diabetic macular edema, and ERM [3,[14][15][16]. On the other hand, the impaired photoreceptor layer integrity can significantly worsen the prognosis for vision improvement, despite the properly performed, uncomplicated vitrectomy [14].…”
Section: Discussionmentioning
confidence: 99%
“…[19], J. Michalewski и соавт. [20] и H. Koo и соавт. [13] выявлена статистически значимая корреляция между МКОЗ и об-щей толщиной сетчатки в фовеа, тогда как другие авторы данную корреляцию не подтверждают [21].…”
Section: морфофункциональная характеристика изменений сетчатки у пациunclassified
“…Особое значение для оценки зрительных функций при иЭРМ придается соединению ВС/НС фоторецепто-ров [20,22]. Гиперрефлективность слоя ВС/НС на срезах ОКТ -результат различия рефракционных индексов ме-ста контакта ВС/НС фоторецепторов и окружающих структур наружной сетчатки.…”
Section: морфофункциональная характеристика изменений сетчатки у пациunclassified
“…2,3 Clinical presentation of IEMM varies on the degree of deterioration in macular microarchitecture. 5,6 In clinical practice, dilated fundoscopic examination and optical coherence tomography (OCT) imaging are usually sufficient for the diagnosis. Furthermore, OCT allows the physician to follow-up changes in retinal microstructure, particularly integrity of photoreceptor inner segment/outer segment (IS/OS) junction, which was found associated with postoperative visual improvement.…”
Section: Introductionmentioning
confidence: 99%